A Multi‐Wall Sn/SnO2@Carbon Hollow Nanofiber Anode Material for High‐Rate and Long‐Life Lithium‐Ion Batteries. Issue 6 (17th January 2020) - Gao, Songwei; Wang, Nü; Li, Shuai; Li, Dianming; Cui, Zhimin; Yue, Guichu; Liu, Jingchong; Zhao, Xiaoxian; Jiang, Lei; Zhao, Yong
Abstract: Multi‐wall Sn/SnO2 @carbon hollow nanofibers evolved from SnO2 nanofibers are designed and programable synthesized by electrospinning, polypyrrole coating, and annealing reduction. The synthesized hollow nanofibers have a special wire‐in‐double‐wall‐tube structure with larger specific surface area and abundant inner spaces, which can provide effective contacting area of electrolyte with electrode materials and more active sites for redox reaction. It shows excellent cycling stability by virtue of effectively alleviating pulverization of tin‐based electrode materials caused by volume expansion. Even after 2000 cycles, the wire‐in‐double‐wall‐tube Sn/SnO2 @carbon nanofibers exhibit a high specific capacity of 986.3 mAh g −1 (1 A g −1 ) and still maintains 508.2 mAh g −1 at high current density of 5 A g −1 . This outstanding electrochemical performance suggests the multi‐wall Sn/SnO2 @ carbon hollow nanofibers are great promising for high performance energy storage systems. Abstract : Multi‐wall Sn/SnO2 @carbon composite hollow nanofibers were prepared by electrospinning and carbonization reduction. They have solid wire core that is wrapped by a double‐wall‐tube. This wire‐in‐double‐wall‐tube strategy perfectly combines high energy density and high cycling stability. It produces superior electrochemical performance, with a capacity of 986.3 mAh g −1 at 1 A g −1 and 508.2 mAh g −1 at 5 A g −1 after 2000 cycles.